Rheology of self-compacting concrete mortar phase - Oliveira, Luiz Antonio Pereira de (2018)
The workability of self-compacting concrete is strongly dependent of its mortar phase rheological behaviour. In fact, some powders materials and the new generation superplasticizer have been employed to attain the self-compactability in concrete mixtures. Normally, the SCC mixtures present a high amount of mortar in their composition. Thus, the SCC mortar phase has a very important influence on the SCC rheological behaviour that is also influenced by the materials used to compose the mortar phase. Some rheological properties as plastic viscosity and thixotropy are important to define the self-compacting concrete workability. These properties are critical mainly when filling the formwork on site to achieve the compactness of the final product, since this type of concrete is applied without any vibration or other form of compaction. Thus, an approach of SCC rheological behaviour by previous mortar phase behaviour knowledge is especially relevant. This article describes an experimental study to evaluate the influence of different SCC mortar phase composition on the rheological behaviour. Powders materials of different nature, some them from wastes materials, are used to compose the mortar phase. The rheological parameters as relative yield stress and plastic viscosity was determined with a rheometer and others tests as slump flow (spread cone) and fluidity (v-funnel) were also used. The results provided a comparative and critical analysis of the relative influence of the mortars materials on the rheological parameters. It was found that the rheological behaviour of SCC mortar phase is represented by the Herschel-Buckley model.